Fungos urbanos em Araras-SP: levantamento bibliométrico, caracterização laboratorial e ciência cidadã no Parque Ecológico e Cultural Gilberto Rüegger Ometto - Souza, Laiane Rodrigues de (Universidade Federal de São Carlos, 2026)
Fungi perform essential ecological functions in natural and urban ecosystems, including organic matter decomposition, nutrient cycling, symbiotic interactions, and biodiversity maintenance. Nevertheless, urban funga remains poorly documented and discussed, particularly at the municipal scale. This study aimed to investigate fungi associated with the Gilberto Rüegger Ometto Ecological and Cultural Park, in Araras, São Paulo, Brazil, by integrating three complementary approaches: a regional bibliometric survey, field collection and laboratory characterization of macrofungi, and analysis of participatory records generated through citizen science. The bibliometric survey systematized academic works and scientific articles related to fungi in Araras and surrounding municipalities, extracting information on biological material origin, taxa cited, type of study, and recurring themes. In the field, five macrofungal specimens were recorded in the Ecological Park, mainly associated with woody substrates. Three samples were considered viable for cultivation and laboratory characterization, including fragment isolation, macroscopic colony description, microscopy, preliminary enzymatic assays, and preservation in a local fungal collection. In parallel, records from the BioFuturo na Cidade project and the iNaturalist platform were analyzed to assess the contribution of citizen science to the recognition of urban fungi in Araras. The results indicate that regional fungal research is strongly associated with agricultural topics, biological control, and plant growth promotion, whereas urban fungi and macrofungi in green areas remain underexplored. Laboratory characterization allowed the separation of morphotypes, the registration of colonial and microscopic differences, and the initial preservation of isolates. Citizen science data expanded the visibility of fungi in the municipality, although limitations related to photographic quality, geolocation, and taxonomic resolution were observed. Together, the findings show that bibliometrics, laboratory collection, and citizen science are complementary approaches for building an initial knowledge base on the urban funga of Araras, São Paulo.
Urban fungi in Araras-SP: bibliometric survey, laboratory characterization and citizen science at the Gilberto Rüegger Ometto Ecological and Cultural Park
Keywords: Funga urbana; Macrofungos; Biodiversidade; Coleção fúngica; iNaturalist; Ciência cidadã; Urban funga; Macrofungi; Biodiversity; Fungal collection; Citizen science; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; 15. Vida Terrestre; 11. Cidades e Comunidades Sustentáveis